An Analysis of Current Sustainability of Mexican Cities and Their Exposure to Climate Change - Estrada, Francisco; Velasco, Julián A.; Martinez-Arroyo, Amparo; Calderón-Bustamante, Oscar (Frontiers in Environmental Science, 2020)
The increasing demand for goods and services in cities around the world due to a rapidly growing urban population is pushing the socioecological systems that support them to their limits. The complexity of urban socioeconomic and environmental systems and their interactions generate a challenging multidimensional decision problem. In response, governments around the world are currently generating a variety of measurements that aim to portrait the main factors that are related to the level of sustainability that a city shows. While the objective of these efforts is to help in the process of urban policy making, these measures are often hard to interpret and do not lend to discover underlying characteristics that may be common among a group of cities. Moreover, these measures are typically focused on describing the current state and omit future challenges such as climate change, which may significantly affect any evaluation of urban sustainability. Recently, the Institute of Ecology and Climate Change (INECC) of Mexico produced a dataset of 36 sustainability related variables for over 100 cities that has the objective of helping federal and state level governments defining sustainable urban strategies. Here we use multivariate statistical techniques to 1) decrease the dimensionality of the dataset and find indices that could be more useful to decision makers; 2) find commonalities among cities include in the dataset in order to help in designing urban strategies for cities with similar characteristics; 3) cities are ranked in terms of their sustainability and characteristics and; 4) the sustainability ranking is compared to estimates of how much the current climate in each of these cities is expected to change during this century, which would add further challenges to maintain or improve urban sustainability.